Disseminating Renewable Energy Products in Bangladesh: Implications of Solar Home System Adoption in Rural Households - Khan, Tahsina; Khanam, Shamasunnahar (AIUB Journal of Business and Economics, 2017)
The electricity sector of Bangladesh suffers from acute problems in terms of insufficient power generation and a lack of distribution infrastructure. In this context, the present study explores the renewable energy interventions to promote rural electrification through Solar Home Systems. By conducting key informant interviews and filed observations, this paper sheds light on the distribution of Solar Home Systems in rural households, most of which have been installed through micro-finance schemes provided the by Government and Non-government organizations. In addition to this, the paper also calls for research attention on the fact that even though the SHS program is commercially viable and socially acceptable, there exits some technical and managerial constraints which should be brought under attention of the policy makers and stakeholder institutions for ensuring the advancement of SHS usage in the rural market. With this backdrop, the research adds value to the present literature in the field of improving rural electrification.